2013
DOI: 10.1111/jac.12039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Drought Tolerance of Maize, Sweet Sorghum and Sorghum‐Sudangrass Hybrids

Abstract: In drought-prone environments, sweet sorghum and sorghum-sudangrass hybrids are considered worthy alternatives to maize for biogas production. The biomass productivity of the three crops was compared by growing them side-byside in a rain-out shelter under different levels of plant available soil water (PASW) during the growing periods of 2008 to 2010 at Braunschweig, Germany. All crops were established under high levels of soil water. Thereafter, the crops either remained at the wet level (60-80 % PASW) or wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 25 publications
5
63
0
6
Order By: Relevance
“…Different crop varieties or species may be grown in comparison to A1 [79]. In drought-prone environments, for example, sweet sorghum and sorghum-sudangrass hybrids were tested as alternatives to maize for biogas production in Germany [80]. Like in A1, the combined systems do not differ from pure food/fodder systems in their farming intensity and hence are most likely to have negative effects on biodiversity.…”
Section: B1: First-generation Energy Crop Production On Economically mentioning
confidence: 99%
“…Different crop varieties or species may be grown in comparison to A1 [79]. In drought-prone environments, for example, sweet sorghum and sorghum-sudangrass hybrids were tested as alternatives to maize for biogas production in Germany [80]. Like in A1, the combined systems do not differ from pure food/fodder systems in their farming intensity and hence are most likely to have negative effects on biodiversity.…”
Section: B1: First-generation Energy Crop Production On Economically mentioning
confidence: 99%
“…Some studies have shown greater biomass production for biomass sorghum than other C4 species, including maize and switchgrass (Hallam et al, 2001). Sweet sorghum, a variety with sugar-rich stems (Rooney et al, 2007), and grain sorghum, both with deep, extensive roots (Rooney et al, 2007;Zegada-Lizarazu et al, 2012), produced comparable biomass to maize when water was not a limiting factor, and more biomass than maize in water limited environments (Farré & Faci, 2006;Schittenhelm & Schroetter, 2014). Sweet sorghum was found to be less sensitive to drought than maize (Zegada-Lizarazu et al, 2012), and more water-useefficient than maize and other major grain crops (Steduto et al,1997;Katerji & Mastrorilli, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…MS frente a Altura de plantas de maíz. Schittenhelm & Schroetter (2014), comparando la MS de plantas de maíz con su altura, encontraron que las plantas con altura media de 280 cm tenían una producción de MS de 1.910 g m -2…”
Section: Figura 1 Ms Frente a Dde En Maízunclassified